Current incidence of venous thromboembolism and comparison with 1998: a community-based study in Western France - Delluc, Aurélien; Tromeur, Cécile; Le Ven, Florent; Gouillou, Maelenn; Paleiron, Nicolas; Bressollette, Luc; Nonent, Michel; Salaun, Pierre-Yves; Lacut, Karine; Leroyer, Christophe; Le Gal, Grégoire; Couturaud, Francis; Mottier, Dominique; for the EPIGETBO study group (Thrombosis and Haemostasis, 2016)
In 1998 we estimated the incidence of venous thromboembolism (VTE) to be 1.8/1,000 per year. The aim of this study was to compare current VTE incidence to that observed in 1998. We prospectively recorded all cases of symptomatic pulmonary embolism (PE) and deep vein thrombosis (DVT) of the lower limbs diagnosed between March 1, 2013 and February 28, 2014 in hospitals and in the community, using the same method and geographic area than in 1998. The 2013 incidence rates of VTE were computed and compared with those of 1998 using age- and sex-specific standardised incidence ratios (SIRs). In 2013, we recorded 576 VTE cases (279 isolated DVT and 297 PE ± DVT). Among 367,911 inhabitants, the overall incidence of VTE was 1.57/1,000 (95 % CI 1.44–1.69). The overall VTE incidence was significantly lower in 2013 as compared with 1998: SIR 0.72 (95 % CI 0.67–0.79) as well as the incidence of isolated DVT: SIR 0.53 (95 % CI 0.47–0.60); conversely, the overall incidence of PE was unchanged: SIR 1.10 (95 % CI, 0.98–1.23) despite an increase in the incidence of isolated PE: SIR 1.29 (95 % CI, 1.10–1.52). In 1998, 4.4 % of PE cases were diagnosed using CTPA as compared with 73.7 % in 2013 (p < 0.001). In conclusion, between 1998 and 2013, the incidence of symptomatic DVT decreased. Conversely, we found no similar reduction in the incidence of symptomatic PE; whether this is due to changes in diagnostic tests and algorithms in the management of suspected PE requires further investigations.Supplementary Material to this paper is available online at www.thrombosis-online.com.
Keywords: Venous thromboembolism; epidemiology